Starrageen softgel - Mohd Daud, Jamaluddin; Abd Rashid, Nur Suhaidah; Rabbani, Mohd Afif (2010)
The instability of gelatin based capsule when filled with certain liquid pharmaceutical formulations has drawn a great concern among scientists. Moreover, the costly expense to obtain gelatin from its sources and its limited availability are also the major disadvantages of using gelatin in industrial scale. The source of gelatin can be a problem for potential areas of use or for particular consumers, especially in obtaining the hallal gelatin. An alternative composition from a mixture of carrageenan and a number of starches to replace gelatin in the production of soft gel capsules for packaging of liquid drugs has been discovered. This gelatin replacer has the properties equivalent to those of the gelatin in forming soft gel capsules.